Antimicrobial dual-crosslinked hydrogel synergizes bioengineered extracellular vesicles for enhanced diabetic wound healing - Yikun Ju; Pu Yang; Xiangjun Liu; Rui Wu; Naisi Shen; Naihsin Hsiung; Anqi Yang; Chi Zhang; Bairong Fang; Liangle Liu (Materials Today Bio)
Diabetic wound healing remains a major clinical challenge owing to impaired angiogenesis, prolonged inflammation, and bacterial infection. Stem cell-derived extracellular vesicles (EVs) offer a promising solution for improving diabetic wound healing. The biological activity of EVs can be increased by engineering modifications. Antimicrobial hydrogel dressings combined with bioengineered EVs, will provide a good solution to the problem of difficult healing of diabetic wounds. Therefore, this study aims to investigate the potential of BCL-2-engineered EVs to enhance wound healing in a diabetic mouse model. BCL-2 engineered adipose mesenchymal stem cells were constructed using the lentiviral embedding method, and analyzed their transcriptional changes through transcriptome sequencing. Their secreted EVs were isolated and characterized by proteomic sequencing. Integrating bioinformatics analysis, we found that BCL-2 engineered EVs may play a powerful role in angiogenesis and tissue repair. Furthermore, we developed an antimicrobial hydrogel based on epsilon-poly-lysine and hyaluronic acid to encapsulate them. The hydrogel-EVs system demonstrated a comprehensive promotion of wound healing, including increased angiogenesis, enhanced cell proliferation, reduced inflammation, and improved tissue architecture. These findings highlighted the potential of BCL-2-engineered EV-loaded antimicrobial hydrogels as a novel strategy for managing diabetic wounds, providing a promising alternative to overcome the limitations of current therapeutic approaches.